Analisis Video Pola Hidup Lansia di Kota Tokyo - Oktavia, Rani; Arfianty, Rani (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
This journal discusses the lives of the elderly in the city of Tokyo, Japan, which is experiencing significant demographic changes and has a rich culture. The elderly in Japan are respected as guardians of traditional values, but face challenges such as changes in family structure, social isolation, health problems, and the impact of economic and technological change. Previous research has explored eating patterns, cultural values such as ikigai, the digital divide, and intergenerational interactions. This research adopts a unique approach using video analysis to further understand the lifestyle of elderly people in the city of Tokyo. Research methods involve qualitative analysis, document analysis, and visual observation. Qualitative findings involve the social dynamics, activity patterns, and emotional well-being of older adults. Document analysis highlights senior-friendly urban policies and social/recreational programs. Visual observations reveal emotional expressions and inequalities in the accessibility of public facilities. The results of the integration of findings from the three methods show that social involvement and various activities contribute to the well-being of the elderly. Accessibility challenges need to be addressed through inclusive urban planning, while public policy can play an important role in creating an environment that supports the quality of life of seniors. Emphasis is also placed on the emotional aspects and mental well-being of the elderly. By synthesizing these findings, the research provides a strong basis for the development of effective policies and programs in supporting the well-being of older people in a dynamic urban context and the findings from these three methods, we can form a holistic view of the lives of older people in the city of Tokyo.